2014
DOI: 10.1007/s10802-014-9945-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Moderators of the Link Between Parent and Child Anxiety Sensitivity: The Roles of Gender, Positive Parenting, and Corporal Punishment

Abstract: A substantial body of literature suggests that anxiety sensitivity is a risk factor for the development of anxiety problems and research has now begun to examine the links between parenting, parent anxiety sensitivity and their child’s anxiety sensitivity. However, the extant literature has provided mixed findings as to whether parent anxiety sensitivity is associated with child anxiety sensitivity, with some evidence suggesting that others factors may influence the association. Theoretically, specific parenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 44 publications
5
19
2
Order By: Relevance
“…The CASI is an 18-item measure on which participants use a 3-point scale (1 = None , 2 = Some , 3 = A lot ) to answer questions such as “it scares me when my heart beats fast.” Items are summed to yield global AS level scores (Silverman et al, 1991; Wright, London, & Field, 2011). Prior work supports the validity and reliability of the CASI; the internal consistency estimate for the global factor from the current study also aligned with previously published work ( α = 0.74; Graham & Weems, 2015; Knapp et al, 2013).…”
Section: Methodssupporting
confidence: 89%
“…The CASI is an 18-item measure on which participants use a 3-point scale (1 = None , 2 = Some , 3 = A lot ) to answer questions such as “it scares me when my heart beats fast.” Items are summed to yield global AS level scores (Silverman et al, 1991; Wright, London, & Field, 2011). Prior work supports the validity and reliability of the CASI; the internal consistency estimate for the global factor from the current study also aligned with previously published work ( α = 0.74; Graham & Weems, 2015; Knapp et al, 2013).…”
Section: Methodssupporting
confidence: 89%
“…Some limitations on this study should be mentioned. First, several authors have shown that gender differences appear to be related to parental rearing practices, which differ for girls and boys (Ginsburg & Silverman, ; Graham & Weems, ; Muris et al ., ). In this study, the sample size was insufficient to conduct separate regression analyses for girls and boys.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of the potential parental contributions to child AS, but certain specific mechanisms might condition the relationship between child AS and parental factors (Francis & No€ el, 2010). For example, Graham and Weems (2015) observed that parenting behaviours (e.g., positive parenting: praise, compliments) moderate the association between parental and child AS. The parent's gender has been postulated to be a possible moderator of the association between parental factors and child AS (Francis & No€ el, 2010).…”
mentioning
confidence: 99%
“…In addition, corporal punishment is linked to the child's reduced sense of control over the situation, and to a reduced ability to control body reactions, which increases the feeling of anxiety. 52 Reduced control, which is transmitted to one's perception in adulthood, can increase impulsivity in raising children, thus allowing the increased use of corporal punishment.…”
Section: Intergenerational Transmission Of Corporal Punishmentmentioning
confidence: 99%